Highlights 2016 - Yearly status report EDEN Initiative - Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Vrakking, Vincent (2016)
SpaceX founder Elon Musk outlines his plans for a human presence on Mars, ESA pushes its ambitions for an international Moon village, and DLR establishes the Orbital Hub concept as a possible ISS successor. In this sense, 2016 marked an outstanding year for human spaceflight. The EDEN team contributed to these ambitions with technical solutions and paved the way on the political agenda in the same motivated manner like the years before. The EDEN ISS project gained speed and the successful development of various systems was accomplished. The Critical Design Review marked an important milestone, and in September, the Mobile Test Facility was delivered to DLR for the Assembly, Integration, and Test phase. Paul Zabel, who will live for one year in Antarctica, received basic training on hydroponic plant cultivation and treatment at our EDEN ISS partner University of Wageningen (NL). This way the EDEN team is prepared for the space analogue mission to Antarctica in 2018. Another highlight was the continued progress within the DLR internal project C.R.O.P, where tomatoes were successfully tested in the lab’s clean room with the dedicated urine-based nutrient solution. This joint research project between DLR-RY and DLR-ME will further push the boundaries of Bio-regenerative Life Support Systems. Establishing a clear political agenda and pushing for more international collaboration is essential in the space sector and is actively pursued by the EDEN team. Here, the White Paper could officially be published, after two years of coordination under the lead of the EDEN group. This unique position paper outlines the strategic roadmap of the space agriculture community. Like two years ago, the EDEN team assisted in the organization of the AGROSPACE event together with AeroSekur and the University of Arizona. Preceding the conference the team organized the European-Chinese Collaboration Workshop on Closed-loop Technologies for Space, Antarctica and Urban Areas. Leading experts from China, Germany and European industry ...